2018
DOI: 10.1038/s41598-018-24904-z
|View full text |Cite
|
Sign up to set email alerts
|

Tau Internalization is Regulated by 6-O Sulfation on Heparan Sulfate Proteoglycans (HSPGs)

Abstract: The misfolding and accumulation of tau protein into intracellular aggregates known as neurofibrillary tangles is a pathological hallmark of neurodegenerative diseases such as Alzheimer’s disease. However, while tau propagation is a known marker for disease progression, exactly how tau propagates from one cell to another and what mechanisms govern this spread are still unclear. Here, we report that cellular internalization of tau is regulated by quaternary structure and have developed a cellular assay to screen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
144
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 42 publications
4
144
0
Order By: Relevance
“…This structural diversity mediates a wide range of protein-GAG interactions of varying specificity and affinity. Hp/HS has been involved in a wide and growing array of physiological and pathophysiological processes, usually mediated through interactions between proteins and a subset of Hp/HS structures 4-6 . While the importance of oligosaccharide structure has been established in many functions of Hp/HS, understanding the structures that underlie any of the various functions is highly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…This structural diversity mediates a wide range of protein-GAG interactions of varying specificity and affinity. Hp/HS has been involved in a wide and growing array of physiological and pathophysiological processes, usually mediated through interactions between proteins and a subset of Hp/HS structures 4-6 . While the importance of oligosaccharide structure has been established in many functions of Hp/HS, understanding the structures that underlie any of the various functions is highly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…This process was dependent on heparan sulfate proteoglycans (HSPGs). HSPGs have recently been shown again to play a role in tau internalisation, as the knockdown of Hs6st1 (a gene involved in HSPG synthesis) by CRISPR in H4 human neuroglioma cells and iPSCs resulted in a decreased tau uptake in vitro 110 . This study also demonstrated a similar decrease in tau uptake upon knockdown of dynamin 110,111 , a large GTPase involved in endocytosis 112 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…HSPGs have recently been shown again to play a role in tau internalisation, as the knockdown of Hs6st1 (a gene involved in HSPG synthesis) by CRISPR in H4 human neuroglioma cells and iPSCs resulted in a decreased tau uptake in vitro 110 . This study also demonstrated a similar decrease in tau uptake upon knockdown of dynamin 110,111 , a large GTPase involved in endocytosis 112 . Tau aggregates were further shown to colocalise with the fluid-phase uptake marker dextran in C17 cells, suggesting that aggregates also enter these cells through engulfment by the membrane in an endocytic pathway 57 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Upon measurement of recombinant and AD‐derived tau aggregates based on tau repeat domain (RD; amino acids 243–375) and in cultured HEK293cells and primary cultured neurons, the minimum tau assembly has been shown to be a minimum of three units (trimers) . In a more recent study on a variety of cell models, including human CNS‐derived cell lines and iPS‐derived neurons, full‐length human tau (2N4R) is also internalised efficiently, however, for both monomeric and oligomeric tau . In another study, it was shown that tau fibrils could not be taken up, which suggests that there is a range of lengths of the tau species that are taken up by cells; however, additional experiments are needed to elucidate the conflicting results regarding the uptake or not of tau monomers.…”
Section: Transcellular Spreading Of Taumentioning
confidence: 99%
“…In a more recent study on a variety of cell models, including human CNS‐derived cell lines and iPS‐derived neurons, full‐length human tau (2N4R) is also internalised efficiently, however, for both monomeric and oligomeric tau . In another study, it was shown that tau fibrils could not be taken up, which suggests that there is a range of lengths of the tau species that are taken up by cells; however, additional experiments are needed to elucidate the conflicting results regarding the uptake or not of tau monomers.…”
Section: Transcellular Spreading Of Taumentioning
confidence: 99%